The intra-class heterogeneity of immunophenotyping and immune landscape in oesophageal cancer and clinical implications. (1st January 2021) - Xie, Yujie; Shi, Xiaoshun; Chen, Ying; Wu, Bomeng; Gong, Xiaolin; Lu, Weicheng; Lin, Wanli
Abstract: Background: The response rate and survival benefit of immunotherapy vary among patients, implying specific immune status of an individual could be associated with the effect of immunotherapy. However, in-depth studies of immune subtypes (ISs), immune landscape and tumour microenvironment of oesophageal cancer (ESCA) and their clinical implications are less reported. Methods: We first accessed data from publicly available databases and preprocessed it based on a standard protocol. Then, ISs were identified by unsupervised learning. Thereafter, the association of these ISs and tumour mutation burden (TMB), biomarkers of chemotherapy-induced immune response, tumour markers were also assessed. In addition, the immune characteristics, immune landscape, co-expression network of immune genes, and clinical implications were visualized and analysed. Results: We identified three immunoclusters based on immune-associated genes with intra-class heterogeneity and prognostic value. Cluster-specific associations with TMB, markers of chemotherapy-induced immune response, and tumour markers were revealed. A 4-gene signature (risk score= −0.16514291× BHLHE22 −0.03964046× MXRA8 −0.15242778× SLIT2 −0.05553572× SPON1 ) based on co-expressed genes in the immunoclusters was developed and externally validated. Conclusions: In summary, we identified clinically relevant immunoclusters in both adenocarcinoma and squamous cell carcinoma of oesophagus, revealing the necessity of assessing the complexity and diversity of immune microenvironment for cancer immunotherapy.